(untitled) (Annals of Medical Research, 2021)
Aim: Coronary arterial dominance is described on the basis of artery that feeds the posterior descending artery (PDA) and posterolateral branches. The literature lacks any data on long-term influence of coronary arterial dominance on non-obstructive coronary artery disease (CAD). This research therefore aims to study the influence of coronary dominance on long-term mortality in patients with non-obstructive CAD. Material and Methods: This retrospective research involved 592 patients who had been subjected to elective coronary angiography. On the basis of coronary artery dominance pattern, the subjects were categorized into two groups i.e. left dominance group (n=84) and right dominance group (n=508). Patients demonstrating co-dominance were placed in the left dominance group. All-cause mortality was considered to be the primary endpoint of the research. Results: Most (65%, 382) of the patients included in the study were male. Average age of subjects was 60±9.7 years. Right coronary dominance was demonstrated by 85.8% patients while left coronary dominance was demonstrated by 14.2% patients. 42 deaths occurred as per the recordings made in a follow-up of 48±12.9 months. In case of right dominance group, mortality rate was 6.1% and in case of left dominance group, it was 13.1% (p=0.021). Findings of a multivariate regression analysis indicated that diabetes mellitus (HR: 2.008, 95% CI:1.034–3.902, p=0.04) and left dominance (HR:1.55, 95%CI: 1.094–2.200, p=0.014) can serve as independent predictors of mortality in these patients. Conclusion: Left dominance has been found to be associated with higher rates of mortality in non-obstructive CAD patients during a long-term follow up.